2021
DOI: 10.1525/elementa.2021.00142
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the variation in rainwater acidity in 24 Chinese cities during 1982–2018

Abstract: Rainwater is an essential pathway to remove fine particulate matter and dissolved atmospheric pollutants (e.g., SO2, HNO3, and NH3). Acid rain (pH < 5.6) has been a severe environmental issue in China since the 1970s, adversely impacting ecosystem health. This study focuses on the influence of anthropogenically induced anions (SO42– and NO3–) and alkaline cations (Ca2+ and NH4+) on acid rain in Chinese cities. In this review, cities with high population density east of the Hu Huanyong Line that divides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 104 publications
(157 reference statements)
0
25
0
Order By: Relevance
“…By contrast, the potential Cl − inputs from the anthropogenic domestic sewage in urban region may be assuaged by various landscape setting and the well-mixed processes of river water, further resulting in a low concentration of riverine Cl − . Moreover, although previous work have revealed that rainwater NO 3 − could be a significant contributor (even up to 71%) of riverine NO 3 − during storm-frequency season [35], however, the river water NO 3 − concentration (0.19 ± 0.13 meq/L) in the study period (dry season) was much higher than the karst rainwater NO 3 − concentration (typically < 0.04 meq/L) [36][37][38]. Therefore, the contribution of wet deposition to Chishui River water NO 3 − is very limited.…”
Section: Stoichiometry-revealed Sources Of Solutesmentioning
confidence: 72%
“…By contrast, the potential Cl − inputs from the anthropogenic domestic sewage in urban region may be assuaged by various landscape setting and the well-mixed processes of river water, further resulting in a low concentration of riverine Cl − . Moreover, although previous work have revealed that rainwater NO 3 − could be a significant contributor (even up to 71%) of riverine NO 3 − during storm-frequency season [35], however, the river water NO 3 − concentration (0.19 ± 0.13 meq/L) in the study period (dry season) was much higher than the karst rainwater NO 3 − concentration (typically < 0.04 meq/L) [36][37][38]. Therefore, the contribution of wet deposition to Chishui River water NO 3 − is very limited.…”
Section: Stoichiometry-revealed Sources Of Solutesmentioning
confidence: 72%
“…Due to the significance of LWC to HMS production and reversal, it is likely that aqueous aerosols, fog, cloud droplets, and possibly ice crystals will be most impactful on HMS production. Because the rainwater pH of areas such as the Western U.S. and Eastern China can reach much less acidic pH levels due to increased ammonia emissions, it is likely that these areas will be more susceptible to HMS 690 production (Keresztesi et al, 2020;Qu and Han, 2021). Together, these conditions indicate that highly polluted areas which experience higher pH and greater LWC will likely be influenced by this chemistry.…”
Section: Model Hms Sensitivity Analysis 650mentioning
confidence: 99%
“…Wet precipitation is an essential pathway to scavenge pollutants from atmosphere (Qu et al, 2021). Over 90% of the total amount of pollutants present in the atmosphere can be scavenged through wet deposition (MacDonald et al, 2018;Mehr et al, 2019;Gromping et al, 1997).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%